Developments towards the comprehensive analysis of petrochemical streams - Rohwer, Egmont Richard (University of Pretoria, 2018)
Pertrochemical products derived from crude oil and Fischer-Tropsch (FT) processes contain a variety of compounds over a wide carbon number range and a large number of fuels and chemicals are produced during product workup. The characterisation of these fuels and chemicals as well as intermediate process streams is very important to control conversion processes. The analysis of any one of these phases is very challenging. Typical oil phase samples may contain thousands of compounds. In many cases, complete characterisation of these complex samples is possible with comprehensive two-dimensional gas chromatography (GC×GC), but even with the increase in separation power obtained by comprehensive GC, peak co-elution still occurs when complex samples are analysed. In this work chromatographic techniques were investigated and the hyphenation of these techniques was evaluated, addressing some of the remaining analytical challenges in petrochemical analysis. The on-line hyphenation of supercritical fluid chromatography (SFC) to a GC×GC system as a pre-separation technique was successfully developed to address the challenge of the separation between cyclic and non-cyclic alkenes and alkanes. The developed SFC preseparation method also pre-separated the sample of interest into other chemical groups (saturates, unsaturates, oxygenates and aromatics) for further characterisation by GC×GC. On-line hydrogenation after GC×GC separation was successfully developed to address the challenge of distinguishing between isomeric cyclic and double bond containing compounds with the same (two or more) double bond equivalents. The number of rings and alkene double bonds in specific compounds could be determined from the mass spectra of the compounds before and after hydrogenation in a complex petrochemical sample requiring GC×GC separation. A high temperature (HT)-GC×GC method was developed to replace titrimetric procedures traditionally used for the control of oxidation processes of heavy paraffinic fractions. The advantages of the developed HT-GC×GC method include the selective quantification of oxygenate classes and obtaining the concentration for each oxygenate class by carbon number. This allows the optimisation of conditions used to oxidise heavy paraffinic fractions. The challenge of the identification of oxygenates in these oxidised heavy paraffinic fractions was also addressed with the development of a method that pre-separates the oxygenates before subsequent analysis by gas chromatography mass spectrometry, with the use of a supersonic molecular beam (GC-SMB-MS). The EI spectra with enhanced molecular ions obtained by GC-SMB-MS aided tremendously in the identification of oxygenates and the advantage of this procedure was illustrated, whereby the heavy oxygenates in an oxidised heavy paraffinic sample could be better identified. This study successfully addressed various analytical challenges in the field of petrochemical analysis and the developed techniques may be useful for the comprehensive characterisation of various streams in other areas of petrochemical analysis.